2019
DOI: 10.1063/1.5111558
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved turbulent velocity field reconstruction using a long short-term memory (LSTM)-based artificial intelligence framework

Abstract: This paper focuses on the time-resolved turbulent flow reconstruction from discrete point measurements and non-time-resolved (non-TR) particle image velocimetry (PIV) measurements using an artificial intelligence framework based on long short-term memory (LSTM). To this end, an LSTM-based proper orthogonal decomposition (POD) model is proposed to establish the relationship between velocity signals and time-varying POD coefficients obtained from non-TR-PIV measurements. An inverted flag flow at Re = 6200 was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Srinivasan et al [47] compared deep feed-forward and recurrent LSTM networks for turbulent shear flows prediction. Recently Deng et al [48], used LSTM networks to reconstruct the POD coefficient time series using sub-sampled distributed velocity sensors in an inverted flag flow PIV experiment. A short review of applications of deep NN to fluid mechanics can be found in [49].…”
Section: Neural Network In Fluid Mechanicsmentioning
confidence: 99%
“…Srinivasan et al [47] compared deep feed-forward and recurrent LSTM networks for turbulent shear flows prediction. Recently Deng et al [48], used LSTM networks to reconstruct the POD coefficient time series using sub-sampled distributed velocity sensors in an inverted flag flow PIV experiment. A short review of applications of deep NN to fluid mechanics can be found in [49].…”
Section: Neural Network In Fluid Mechanicsmentioning
confidence: 99%
“…The fully connected neural network was used to predict the time coefficients of POD modes. Similarly, Rahman et al (2019), Deng et al (2019) and Ahmed et al (2019) used LSTM to predict the time coefficients of POD modals, and Miyanawala et al (2019) used CNN to predict the time coefficients of POD modals. And combinations of the CNN and ConvLSTM also been proposed for dimensionality reduction and spatial-temporal modeling of the 3 / 22 flow dynamics by Mohan et al (2019), Hasegawa et al (2019) and Han et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally necessary to use an order reduction to derive some information that could be handled either to model or control the targeted flow. Data-driven methods are nowadays becoming more and more efficient and reliable even for fluid mechanics research 9,17 . Among successful applications, one can cite statistical learning 16 or machine learning 14,35 algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…In an inverted flag flow experiment, Deng et al 9 applied an ANN identification method to reconstruct time-resolved velocity fields from a handful of velocity sensors. It was also proven recently that ANNs can be used to predict the dynamics and reconstruct the time-resolved fields of an experimental Backward-Facing Step (BFS) flow 15 .…”
Section: Introductionmentioning
confidence: 99%